Translating research into practice: Evaluation of an e-learning resource for health care professionals to provide nutrition advice and support for cancer survivors. (January 2015) - Murphy, Jane; Worswick, Louise; Pulman, Andy; Ford, Grainne; Jeffery, Jaana
Summary Background Nurses and other allied health professionals are in a key position to provide appropriate and consistent advice on nutritional issues to support cancer survivors. However gaps in their nutrition knowledge and education warrant the need for enhanced learning as part of their Continued Professional Development (CPD). In the UK there are currently no formally recognised nutrition education programmes. Therefore e-learning offers a solution to provide flexible learning to target this need. Aims This study aimed to develop and evaluate the efficacy of a freely available, internet-based learning resource, for nurses and allied health professionals who provide nutrition, diet and lifestyle advice for cancer survivors. It sought to explore the attitudes and conceptions of the resource and current knowledge base of those involved in the care pathway for cancer survivors. Method The design and development of the e-learning resource were informed by the best available research and policy evidence and in a format to facilitate on-line learning. A robust evaluation strategy incorporated focus groups and telephone interviews to gain in depth insights into the experiences of using the resource. Results Themes included 'Plugging a Gap' which shows an improved knowledge base for nutrition. Information was 'All in One Place' showing that the resource was valued as being within a 'trusted' organisation. 'Everyone Benefits' illustrates how learners felt that the resource provided them with an evidence base, whilst the 'Current and Live' theme captured how professionals felt about the information being up-to-date. Conclusions The project has shown the benefits of interprofessional working to develop an e-learning resource for Health Care Professionals to support cancer survivors in following healthier lifestyles. Positive attitudes and potential improvements in the knowledge base and changes for professional practice were demonstrated. Further research is required to gauge sustained impact in the work environment by embedding the resource as part of CPD.